Comparison of the efficacy of microendoscopic discectomy and percutaneous endoscopic lumbar discectomy for treating adolescent lumbar disc herniation - Lu Mao; Zicong Shen; Weiye Zhu; Kun Wang; Pan Fan; Xiaotao Wu; Lijun Li; Guanyi Liu (Scientific Reports)
Abstract Microendoscopic discectomy (MED) has long been employed as the standard operation for adolescent lumbar disc herniation (ALDH). However, due to iatrogenic injury, it has been suspected to cause adverse effects. Alternatively, percutaneous endoscopic lumbar discectomy (PELD) is considered as effective as MED. Few studies have compared MED and PELD in the treatment of ALDH. The purpose of this study was to compare the possible differences in young patients who underwent MED or PELD. From January 2011 to January 2021, 49 consecutive patients were treated with MED (17 patients) or PELD (32 patients) at the authors institution. Numeric Rating Scales (NRS) scores, Oswestry Disability Index (ODI) and modified MacNab criteria demonstrated significant improvement in both early and late follow-up evaluations (P < 0.01). PELD group resulted in shorter operative times and lower re-operation and complication rate. The PELD group exhibited shorter incision length, length of hospital stay and less intraoperative blood loss than the MED group. Both PELD and MED have demonstrated great efficacy in managing symptomatic ALDH. PELD appears to offer superior control over surgical trauma and promotes rapid recovery compared to MED.